An Analysis of Organizational Demographics and Measuring the Results after Adopting Digital Marketing by SMES of Uttar Pradesh - Priyanka Pradhan, Dr. Devesh Nigam, Dr. C.K. Tewari (International Journal of Advanced Science and Technology, 2020)
Both demand and competition have been changing and are giving pressure to organization to adopt innovative practices. Are innovative strategies worth to opt? There is a need to address the changes after the adoption of technology and innovation.